Demokrasi Deliberatif dalam Pemikiran Intelektual Muslim Indonesia: Analisis Literatur atas Tantangan dan Prospek - Selly Silviawati; Isa Al Ansori (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This study aims to examine how the concept of deliberative democracy is perceived and constructed within the intellectual discourse of Indonesian Muslim scholars. Employing a qualitative approach through literature analysis, data were gathered from academic works, including books, journal articles, and relevant conference proceedings. The analysis was conducted thematically to identify key patterns, categories, and overarching themes. The findings reveal three main points. First, the literature highlights the compatibility between Islam and deliberative democracy through the reinterpretation of shūrā, which is framed as a normative foundation aligned with modern practices of consultation. Second, the study identifies structural and cultural barriers—such as political polarization, elite dominance, and limited public space—that hinder substantive deliberation. Third, it highlights the potential for strengthening deliberative democracy through the integration of Islamic values, particularly by emphasizing maqāṣid al-sharīʿah, the ethics of justice, and the recognition of pluralism. In addition, the research introduces new categories, namely ethical deliberation and the rise of digital deliberation, both of which enrich the Indonesian model of deliberative democracy. Ultimately, the study concludes that deliberative democracy grounded in Islamic ethics is not merely a localized adaptation of Western theory but also makes a significant theoretical contribution to the broader development of deliberative democracy in the global context.